Host IP3R channels are dispensable for rotavirus Ca2+ signaling but critical for intercellular Ca2+ waves that prime uninfected cells for rapid virus spread - Jacob L. Perry; Francesca J. Scribano; John T. Gebert; Kristen A. Engevik; Jenna M. Ellis; Joseph M. Hyser (mBio, 2024)
ABSTRACTRotavirus is a leading cause of viral gastroenteritis. A hallmark of rotavirus infection is increased cytosolic Ca2+ caused by nonstructural protein 4 (NSP4). NSP4 is a viral ion channel that releases endoplasmic reticulum (ER) Ca2+, and the increased Ca2+ signaling is critical for rotavirus replication. In addition to NSP4, host inositol 1,4,5-trisphosphate receptor (IP3R) ER Ca2+ channels may contribute to rotavirus-induced Ca2+ signaling and by extension, virus replication. Thus, we set out to determine the role of IP3R Ca2+ signaling during rotavirus infection using CRISPR/Cas9 IP3R-knockout of MA104 cells stably expressing the GCaMP6s Ca2+ indicator (MA104-GCaMP6s-IP3R-KO). Live Ca2+ imaging showed that IP3R-KO did not reduce Ca2+ signaling in infected cells but eliminated rotavirus-induced intercellular Ca2+ waves (ICWs) and, therefore, the increased Ca2+ signaling in surrounding, uninfected cells. MA104-GCaMP6s-IP3R-TKO cells showed similar rotavirus susceptibility, single-cycle replication, and viral protein expression as parental MA104-GCaMP6s cells. However, MA104-GCaMP6s-IP3R-TKO cells exhibited significantly smaller rotavirus plaques, decreased multi-round replication kinetics, and delayed virus spread, suggesting that rotavirus-induced ICW Ca2+ signaling stimulates virus replication and spread. Inhibition of ICWs by blocking the purinergic receptor P2RY1 (P2Y1), which mediates the ICW Ca2+ signals, also decreased rotavirus plaque size. Conversely, exogenous expression of P2Y1 in LLC-MK2-GCaMP6s cells, which natively lack P2Y1 and rotavirus ICWs, rescued the generation of rotavirus-induced ICWs and enabled plaque formation. In conclusion, this study shows that NSP4 Ca2+ signals fully support rotavirus replication in individual cells; however, IP3R is critical for rotavirus-induced ICWs and virus spread by priming Ca2+-dependent pathways in surrounding cells.IMPORTANCEMany viruses exploit host Ca2+ signaling to facilitate their replication; however, little is known about how Ca2+ signals from different host and viral channels contribute to the overall dysregulation of Ca2+ signaling or promote virus replication. Using cells lacking IP3R, a host ER Ca2+ channel, we delineated intracellular Ca2+ signals within virus-infected cells and intercellular Ca2+ waves (ICWs), which increased Ca2+ signaling in neighboring, uninfected cells. In infected cells, IP3R was dispensable for rotavirus-induced Ca2+ signaling and replication, suggesting the rotavirus NSP4 viroporin supplies these signals. However, IP3R-mediated ICWs increase rotavirus replication kinetics and spread, indicating that the Ca2+ signals from the ICWs may prime nearby uninfected cells to better support virus replication upon eventual infection. This “pre-emptive priming” of uninfected cells by exploiting host intercellular pathways in the vicinity of virus-infected cells represents a novel mechanism for viral reprogramming of the host to gain a replication advantage.